Devario fangae and Devario myitkyinae, two new species of danionin cyprinids from northern Myanmar (Teleostei: Cyprinidae: Danioninae) - Kullander, Sven O. (Zootaxa, 2017)
Devario comprises 38 potentially valid species in southern Asia. Ten species of Devario have been reported so far from Myanmar, six of which belong in the group of striped devarios, with predominantly horizontal stripes in the colour pattern. Among them, records of D. aequipinnatus most likely represent misidentifications. Remaining species of striped devarios in Myanmar are known only from brief descriptions and are in need of taxonomic revision. Devario yuensis and D. deruptotalea, known previously only from India, are here reported for the first time from Myanmar. Devario fangae, new species, is described on the basis of specimens collected in 1998 from small streams in Putao in the extreme north of Myanmar. These streams drain to the Mali Hka River, a tributary of the Ayeyarwaddy River. Devario fangae shares uniquely with D. browni and D. kakhienensis an anterior expansion in width of the middle dark stripe on the side (P stripe). It differs from D. browni and D. kakhienensis in presence of a broad P stripe, wider than adjacent interstripes, vs. narrow, as wide as or narrower than interstripes. Devario fangae is further similar to other species of Devario characterized by three dark stripes (P, P+1, P-1) along the side, but differs from these in having all three stripes wide and of about equal width vs. P stripe wide and P+1 and P-1 stripes much narrower. The largest specimen of D. fangae is 61.0 mm SL. Females are significantly more deep-bodied than males. A specimen of D. aequipinnatus reported from Putao in 1919 probably represents D. fangae. Devario myitkyinae, new species, is described on the basis of specimens collected in 1997 and 1998 from a stream and lake in the Ayeyarwaddy River drainage near Myitkyina in northern Myanmar. It is similar to D. browni and D. kakhienensis, but different from D. fangae in having horizontal stripes on side equal in width, narrow, irregular, and to some extent curved away from horizontal extension. Devario myitkyinae differs from D. browni, D. kakhienensis, and D. fangae in absence of anterior widening of the P stripe. Devario myitkyinae is similar to other species of Devario characterized by three dark stripes (P, P+1, P-1) along the side, but differs from these in having all three stripes irregular and of equal width vs. stripes regular, P stripe wide and P+1 and P-1 stripes much narrower. The largest wild specimen of D. myitkyinae is 68.7 mm SL. A specimen collected near Myitkyina and reported as D. aequipinnatus in 1929 probably represents D. myitkyinae.